If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -3x = 4x + -4x Combine like terms: 4x + -4x = 0 3 + -3x = 0 Solving 3 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -3x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -3x = 0 + -3 -3x = 0 + -3 Combine like terms: 0 + -3 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| 4n+3=3 | | 4t-41=3t-20 | | (x)(5/4)/2=100 | | 8u-52=3u-2 | | (x)(5/4)/2=10 | | 2s+50=5s-13 | | 3x/11-9/11=-3/11 | | -20=-8x+5(x-7) | | -5/6x15 | | 2x-1=-2x+31 | | x=6.5+0.5y | | 3-3i/4i | | 1502x=195-1x | | (2x)^3/4x^2 | | 5w+5=40 | | X=16/cos(64) | | 3(r-16)=9 | | 5x+90=200 | | (2x-2)+(x+1)-x-(x+1)=(2x-9)+(x+1)+(x+8)+x | | [3(7-5)]/2 | | 3(1/3)-1 | | 2x/3-x-1/2 | | 2g+6-5=11 | | 0.4=40/100 | | x*2/3=11/12 | | 6=2-3f-5+5f | | 28c2/6c | | 13-3x-9=8 | | 13x-3(x+4)-5x=7x-(5x-3) | | 7x-2x(x+4)=27 | | 63y^2-30=0 | | x^(1/3)=-1/2 |